A General Methodology to Optimize Flagged Constant Addition - Bhure, Aroondhati; Smriti, P.; Dhanote, Vinay; Anil Kumar, Uppugunduru; Ahmed, Syed Ershad (Journal of circuits, systems, and computers, 2023)
Addition is a ubiquitous operation frequently carried out in most computing applications. Traditionally, three-operand addition is done using either two adders or a carry–save adder. However, there exist applications such as digital signal processing, image processing, floating point arithmetic, etc. wherein among the three operands, one is constant. For such cases, we propose a flagged constant addition methodology, applicable to any constant, to compute the result with the least area, delay and power. The resulting architecture is referred to as general constant flagged adder (GCFA). We propose an Optimized Constant Generation (OCG) algorithm and a Hardware Optimization Algorithm (HOA) to achieve hardware-efficient constant flagged adder. These two algorithms are designed to lower the computational complexity. The OCG algorithm accepts the constant to be added and converts it into an optimized constant. This optimized constant then forms the input to the HOA where the hardware modifications are performed. Unlike the proposed work, the existing flagged adder structures do not provide a general methodology to obtain the optimized constant and hardware for all the constants, resulting from the presence of architectural customization for all constants and word lengths. Exhaustive hardware analyses have been carried out to prove the efficacy of the proposed architecture against the existing designs. Structural Verilog code is synthesized for each to obtain the area, delay and power. Synthesis results show up to 35.85% and 49.24% reductions in area–delay and power–delay products, respectively. The improved speed and lower hardware requirements make the proposed methodology a suitable choice for constant addition.